Developing a thermomechanical and thermochemical model for investigating the cooling rate effects on the distortion of unsymmetrical viscoelastic polymeric composite laminates. (July 2020) - Mobarakian, Mohsen; Safarabadi, Majid; Farahani, Mohammadreza
Abstract: An experimental and semi-analytical study of distortion of asymmetric composite laminates with different cooling rates and lay-ups has been presented. In this study, thermomechanical constitutive equations of thin composite laminates are developed using basic viscoelastic constitutive law considering chemical and thermal effects with time-temperature dependent material properties. To solve a fully scouple problem, both the thermochemical and thermomechanical constitutive equations are formulated. The general heat conduction equation known as the Fourier-Biot equation, viscoelastic laws, Boltzmann superposition principle and composite equations are utilized to formulate thin composite laminates. A static model with constant properties in ambient temperature and a transient model by obtaining constitutive equations are simulated. Results are compared with experimental data. Changing lay-up from cross-ply to angle-ply and then quasi isotropic will increase the value of maximum distortion. Results indicated that the increasing cooling rate will increase the value of the maximum distortion. The differences between FEM results with static analysis of different lay-ups and experimental specimens that cooled in the oven, environment and refrigerator is about 3%, 35% and 55% respectively. The differences between FEM simulation with transient analysis of different lay-ups and experimental specimens that cooled in the environment and the refrigerator is less than 9%. Highlights : The thermomechanical and thermochemical equations are developed for composites based on viscoelastic theory. Experimental results indicate that increasing the cooling rates can significantly increase the deformation. Results indicate that different lay-ups can significantly change the final shape of an asymmetric composite laminate. Results of static analyses are closer to experimental results in the slowest cooling rate that is cooled in the Oven. Only transient analysis with time-temperature dependent material properties could predict the final shape of the asymmetric laminate.